Usual protein intake amount and sources of nursing home residents with (Risk of) malnutrition and effects of an individualized nutritional intervention: An enable study - Seemer, Johanna; Volkert, Dorothee; Fleckenstein-Sußmann, Daniela; Bader-Mittermaier, Stephanie; Sieber, Cornel; Kiesswetter, Eva (Nutrients, 2021)
Nursing home (NH) residents with (risk of) malnutrition are at particular risk of low protein intake (PI). The aim of the present analysis was (1) to characterize usual PI (total amount/day (d) and meal, sources/d and meal) of NH residents with (risk of) malnutrition and (2) to evaluate the effects of an individualized nutritional intervention on usual PI. Forty residents (75% female, 85 ± 8 years) with (risk of) malnutrition and inadequate dietary intake received 6 weeks of usual care followed by 6 weeks of intervention. During the intervention phase, an additional 29 ± 11 g/d from a protein-energy drink and/or 2 protein creams were offered to compensate for individual energy and/or protein deficiencies. PI was assessed with two 3-day-weighing records in each phase and assigned to 4 meals and 12 sources. During the usual care phase, mean PI was 41 ± 10 g/d. Lunch and dinner contributed 31 ± 11% and 32 ± 9% to daily intake, respectively. Dairy products (median 9 (interquartile range 6–14) g/d), starchy foods (7 (5–10) g/d) and meat/meat products (6 (3–9) g/d) were the main protein sources in usual PI. During the intervention phase, an additional 18 ± 10 g/d were consumed. Daily PI from usual sources did not differ between usual care and intervention phase (41 ± 10 g/d vs. 42 ± 11 g/d, p = 0.434). In conclusion, daily and per meal PI were very low in NH residents with (risk of) malnutrition, highlighting the importance of adequate intervention strategies. An individualized intervention successfully increased PI without affecting protein intake from usual sources.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Food source; Individualized intervention; Malnutrition; Nursing home; Protein intake